(untitled) (INTEK : Jurnal Informatika dan Teknologi Informasi, 2026)
This study presents an anonymized retrospective case study of a prominent household appliance distributor in West Sumatra, referred to as PT.XYZ. A critical challenge identified during the operational period was the imbalance between product demand and inventory levels, leading to significant stock accumulation. This research aims to optimize marketing strategies by implementing a decision support system to rank best-selling products using the Fuzzy Analytical Hierarchy Process (F-AHP) method. While the specific business unit has since concluded its active operations, the dataset—comprising 245 product records—remains a robust scientific foundation for modeling consumer behavior in the direct selling sector. Unlike classical AHP, F-AHP integrates fuzzy logic to handle the uncertainty and subjectivity of human judgment in linguistic evaluations. Products were evaluated across four criteria: price, promotional type, product material, and product type. The results demonstrate that F-AHP provides a nuanced ranking, enabling management to prioritize stock effectively. System evaluation through User Acceptance Testing (UAT) yielded a score of 91%, indicating high reliability. This framework offers a sustainable business intelligence model applicable to contemporary direct selling industries facing similar inventory challenges.